MOLECULAR IDENTIFICATION AND MORPHOLOGICAL CHARACTERIZATION OF PATCHOULI (Pogostemon sp.) FROM BATANG REGENCY, CENTRAL JAVA PROVINCE - Hermin Pancasakti Kusumaningrum (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Patchouli (Pogostemon cablin Benth.) is an essential oil-producing plant from Batang Regency that has excellence in patchouli alcohol contents and highly survives in any condition. Molecular identification has been done in the ITS region because DNA sequences in the ITS rRNA region evolved faster than in other areas. This study aimed to get the molecular and morphological identity of patchouli (Pogostemon sp.) from BPP Kabupaten Batang. The study consisted of sample preparation, DNA isolation, amplification, electrophoresis, sequence data analysis, and phylogenetic analysis using MEGA X. All parts of plant were morphologically identified and compared with patchouli from Sidikalang, Aceh, Java, and China. Extraction DNA produced 301.7 ng ?L–1 concentration and 1.93 purity. Amplification of ITS fragment patchouli produced a 670 bp-sized single band. Phylogenetic analysis showed patchouli BPP related to Pogostemon cablin (KR608752.1) with 98% coverage identity. BPP patchouli showed 62,5% morphological similarity with Sidikalang patchouli compared to Java patchouli. In conclusion, BPP patchouli is a Sidakalang patchouli P. cablin that has undergone environmental adaptation.